(untitled) (Journal of the Management Sciences, 2024)
This study examined the effect of financial inclusion on Nigeria’s economic development from 2010 to 2022. From various empirical works reviewed, there is still an insufficient, all inclusive financial system to address the ongoing challenges facing the Nigerian economy which has hindered the promotion of greater inclusion and prosperity for all Nigerians. Using time series data from the Central Bank of Nigeria’s 2022 statistical bulletin, the research explored how variables such as the value of automated teller machine transactions (ATM), the number of commercial bank branches (NCBB), the number of microfinance banks (NMFB), and the volume of point-of-sale machine transactions (VPOST) influence the Human Development Index (HDI). The data analysis, conducted using auto-regressive distributed lag (ARDL) models, revealed that financial inclusion had a negative but statistically insignificant effect over the study period. The study recommends that banks expand access to financial services in rural areas, strengthen regulatory frameworks, support small and medium-sized enterprises (SMEs), leverage technology and innovation, and foster collaborations between the government, financial institutions, and private sector organizations to develop inclusive financial systems.